Makna Komunikasi Keluarga Broken Home - Muhammad Pippo Ferozzi Supriadi; Askurifa'i Baksin (Bandung Conference Series: Communication Management, 2024)
Abstract. Film has a uniqe characteristic to reach a wide public and have a function to broaden a perspective on social issue and culture. One of the films that discusses the issue of post-divorce and family communication is Daren Arofonsky's The Whale. The Whale is a sad and touching story about a man named Charlie who is isolated himself from the world after a divorce and the death of his partner, only to find himself dying with obesity wanting to reconnect with his daughter. This film illustrates how family communication as a bride to reconnecting relationship between family members post-divorce. The purpose of this study is to see the meaning of broken home family communication in The Whale film, this meaning is explained based on the level of reality, level of representation, and level of ideology that is appropriate with John Fiske's semiotic theory. This study was compiled using qualitative analysis methods to describe the meaning family communication on broken home family. Result from this study from the analysis on three level suggesting the effectiveness of family communication to reconnect with a family member post-divorce. Abstrak. Film dengan karakteristik uniknya yang dapat mencakup khalayak luas dan memperluas perspektif mengenai isu sosial dan kultural . Salah satu film yang membahas mengenai isu perceraian dan komunikasi pada angota keluarga adalah film The Whale karya Daren Arofonsky. Film The Whale adalah kisah sedih dan menyentuh tentang seorang pria bernama Charlie yang mengasingkan diri dari dunia setelah percerain dan kematian pasangannya, dimana dirinya yang obesitas dan sekarat ingin berhubungan kembali dengan anak perempuanya. Film ini menggambarkan kekuatan komunikasi keluarga dalam menjadi jembatan dalam memperbaiki kembali hubungan keluarga pasca perceraian. Tujuan dari penelitian ini adalah untuk melihat makna komunikasi keluarga broken home pada film The Whale, makna tersebut dijelaskan dengan berdasarkan level realitas, level representasi, dan level ideologi yang sesuai dengan teori semiotika John Fiske. Penelitian ini disusun dengan menggunakan metode analisis kualitatif untuk mendeskripsikan makna yang terbentuk. Hasil dari ketiga level analisis yang menunjukan efektivitas komunikasi keluarga dalam menjadi jembatan dalam membangun kembali hubungan keluarga pasca perceraian.